Women, work and transport - Wright, Tessa; Budd, Lucy; Ison, Stephen (Transport and sustainability, 2022)
Women, Work and Transportis an international collection that brings together researchers with global expertise in gender and transport work to provide original evidence of the experiences of women working in all transport modes across countries in the Global North and the Global South.